APPROACH HIFZ AL-‘IRDH AND PUBLIC POLICY IN HANDLING BULLYING IN SCHOOLS - Nurul Zhafirah Muslim (Al-ATHFAL: Jurnal Pendidikan Anak, 2024)
This article discusses bullying in school as a serious problem that negatively impacts students’ mental and social well-being. One relevant perspective in dealing with bullying is the hifz al-‘irdh approach, one of the main objectives of maqashid sharia that focuses on protecting the honor and dignity of individuals and offers a way to overcome bullying by instilling moral and ethical values among students. On the other hand, public policy provides the regulatory framework needed to prevent and deal with bullying systematically. This article uses a qualitative approach with policy and normative-theological analysis with hifz al-‘irdh and public policy as theories to be integrated into bullying in schools. The results of this study discuss the synergy between the hifz al-‘irdh approach and public policy in dealing with bullying in schools which highlights the importance of the involvement of all parties, including teachers, parents, and the community in efforts to prevent bullying as a form of effective cooperation instilling supportive moral values. This integrated approach aims to establish a supportive, respectful school environment that not only curbs bullying but also fosters students' overall character growth and well-being. Keywords:  Hifz al-‘Irdh; Public Policy; Bullying; Education